The Garments of Humility - Haddad Bernat, Pedro Humberto (Instituto Tecnológico de Costa Rica, 2024)
If we think about it, it is easy to find plenty of reasons to be humble. Life and human work are tiny and irrelevant compared to the grand scale of the cosmos. Human beings are fallible beings, full of flaws and errors. Forces and agencies other than our own (i.e., mentors, coaches, parents, friends, partners, etc.) are often involved in our achievements and the development of our qualities or talents. Moreover, lack of humility is a pernicious trait for it baulks self-improvement and prevents proper acknowledgement of other people’s potential. In the works J.R.R. Tolkien we learn that it was Melkor’s lack of humility before God what brought about his own downfall. And we also see how Sauron’s arrogance, as a myopia of sorts, prevented him from discovering the plans of his rivals and brought about his own destruction. This paper overviews the traditional conception of humility as a golden mean between arrogance and self-deprecation and shows how The Lord of the Rings – understood within its indissoluble bond with The Silmarillion – is a great tale about how humility overthrows arrogance.